2013
DOI: 10.1002/app.39795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasticizer and curing system on freezing resistance of rubbers

Abstract: At glass transition temperature, T g the rubber compound becomes stiff and brittle and it loses all its rubbery characteristics. This article deals with the changes in T g of rubber blends based on natural rubber and polybutadiene rubber of varying vinyl content having different types and content of plasticizers, different curing systems and its effect on physico-mechanical properties to improve its freezing resistance. The plasticizers used were dioctylphthalate (DOP), tricrecylphosphate (TCP), dioctyladipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
1
22
0
2
Order By: Relevance
“…In some applications (when the working temperature of elastomer part is relatively low) the addition of plasticizer is connected with the decreasing of glass transition temperature, which permit to extend the working temperature range [1][2][3]. Oh and co-workers investigated the influence of selected plasticizers [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In some applications (when the working temperature of elastomer part is relatively low) the addition of plasticizer is connected with the decreasing of glass transition temperature, which permit to extend the working temperature range [1][2][3]. Oh and co-workers investigated the influence of selected plasticizers [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The T g value obtained by DSC experiments is related to segmental chain motion, and it represents the temperature above which the material changes from a stiff solid to a viscous fluid or a rubbery substance. The gehman torsion test provides the relative stiffness at low temperatures as compared with the stiffness at room temperature, and the TR test indicates the elastic recovery at low temperatures …”
Section: Resultsmentioning
confidence: 99%
“…The rubbers containing TOF, R-2, R-1/2, and R-1/2P, exhibited lower minimum torque (M L ) compared to R. All the other flame retarded rubbers showed higher values for M L , due to the reinforcing effect of the solid fillers APP, PANI, and ATH. Rubbers with higher filler loading and reinforcing fillers showed higher values for M L [40,41]. Table 2 presents the maximum torque (M H ), which is a measurement stock modulus [41].…”
Section: Curing Propertiesmentioning
confidence: 99%
“…M H -M L was used to assess the crosslink density of the EPDM rubbers qualitatively [40]. The results showed that the percentages of the M H -M L values decreased with reduced network density, because of increased slippage between the polymer chains.…”
Section: Curing Propertiesmentioning
confidence: 99%